Tides of Time: The Dutch Delta Works as Time-Mediating Climate Adaptation Infrastructure - Huub Dijstelbloem; Victor Toom; Annick de Vries (Tecnoscienza)
The relationship between infrastructure, climate change and time is a crucial but often misunderstood element of climate policy. This article argues that climate adaptation infrastructures mediate between different temporal regimes and can even be said to generate temporal regimes themselves. By examining the development of the Dutch Delta Works, a set of infrastructures initiated after the 1953 North Sea floods that killed more than 1,800 people, the article reconceptualizes the development from the response to the 1953 disaster to its current relationship with the consequences of climate change, in particular rising sea levels, river water inflows and weather fluctuations such as increased rainfall. By situating the development of the Delta Works in relation to Kairos, a period of transition and transformation, rather than Krisis as a response to an immediate disaster, the analysis presents a multifaceted perspective on the relationship between infrastructures, time and temporality. Developing the notion of infrastructural compromises to describe how infrastructures connect to and mediate between different temporal regimes, the analysis examines four episodes, each of which involves a different relationship to time and exemplifies different compromises between temporal regimes. As infrastructure development will be of paramount importance for the development and implementation of climate adaptation policies, it is crucial to arrive at a refined understanding of the relationship between infrastructure and time. A heterogeneous conception of time and temporality is needed to do justice to the mediating role of infrastructures in all these issues and the trade-offs that result from this interaction.